Navigating identities and communities: Insights from the European borderlands - Nadalutti, E.; Guillermo Ramirez, M.; Medeiros, E. (Esercizi Filosofici, 2023)
As Europe contends with globalisation and regionalism, the evolving dynamics of identity and community within European integration are increasingly critical. This paper explores identity formation and community building at the EU’s internal borders, grounded in Aristotelian political theory, particularly insights from “Politics” and “Nicomachean Ethics.” It examines the ‘polis’ as essential for human flourishing and applies this classical framework to modern European border regions. The central research question is: How do European border regions balance local identities within broader networks, and what does this mean for European integration? Using case studies from the b-solutions compendium, the paper hypothesizes that local autonomy and cross-border cooperation enhance both identity preservation and community integration. These case studies highlight practical challenges and solutions in cross-border interactions, emphasizing the importance of harmonizing local and supranational interests. The article outlines Aristotelian philosophical foundations, analyses empirical data, and offers policy recommendations, linking theory with practical insights into Europe’s borderlands.